Single‐shot spiral imaging enabled by an expanded encoding model: Demonstration in diffusion MRI. Issue 1 (21st October 2016) - Wilm, Bertram J.; Barmet, Christoph; Gross, Simon; Kasper, Lars; Vannesjo, S. Johanna; Haeberlin, Max; Dietrich, Benjamin E.; Brunner, David O.; Schmid, Thomas; Pruessmann, Klaas P.
Abstract : Purpose: The purpose of this work was to improve the quality of single‐shot spiral MRI and demonstrate its application for diffusion‐weighted imaging. Methods: Image formation is based on an expanded encoding model that accounts for dynamic magnetic fields up to third order in space, nonuniform static B0, and coil sensitivity encoding. The encoding model is determined by B0 mapping, sensitivity mapping, and concurrent field monitoring. Reconstruction is performed by iterative inversion of the expanded signal equations. Diffusion‐tensor imaging with single‐shot spiral readouts is performed in a phantom and in vivo, using a clinical 3T instrument. Image quality is assessed in terms of artefact levels, image congruence, and the influence of the different encoding factors. Results: Using the full encoding model, diffusion‐weighted single‐shot spiral imaging of high quality is accomplished both in vitro and in vivo. Accounting for actual field dynamics, including higher orders, is found to be critical to suppress blurring, aliasing, and distortion. Enhanced image congruence permitted data fusion and diffusion tensor analysis without coregistration. Conclusion: Use of an expanded signal model largely overcomes the traditional vulnerability of spiral imaging with long readouts. It renders single‐shot spirals competitive with echo‐planar readouts and thus deploys shorter echo times and superior readout efficiency for diffusion imaging and further prospective applications. Magn Reson Med 77:83–91, 2017. © 2016 International Society for Magnetic Resonance in Medicine.